A murine model of the effects of inhaled CuO nanoparticles on cells of innate and adaptive immunity – a kinetic study of a continuous three-month exposure. Issue 7 (9th August 2019) - Holan, Vladimir; Javorkova, Eliska; Vrbova, Kristyna; Vecera, Zbynek; Mikuska, Pavel; Coufalik, Pavel; Kulich, Pavel; Skoupy, Radim; Machala, Miroslav; Zajicova, Alena; Rossner, Pavel
Abstract: The inhalation or application of nanoparticles (NPs) has serious impacts on immunological reactivity. However, the effects of NPs on the immune system are influenced by numerous factors, which cause a high variability in the results. Here, mice were exposed to a three month continuous inhalation of copper oxide (CuO) NPs, and at different time intervals (3, 14, 42 and 93 days), the composition of cell populations of innate and adaptive immunity was evaluated in the spleen by flow cytometry. The ability of spleen cells from exposed and control mice to respond to stimulation with T- or B-cell mitogens by proliferation and by production of cytokines IL-2, IL-6, IL-10, IL-17 and IFN-γ was characterized. The results showed that the inhalation of CuO NPs predominantly affects the cells of innate immunity (changes in the proportion of eosinophils, neutrophils, macrophages and antigen-presenting cells) with a minimal effect on the percentage of T and B lymphocytes. However, the proliferative and secretory activity of T cells was already significantly enhanced after 3 days from the start of inhalation, decreased on day 14 and normalized at the later time intervals. There was no correlation between the impacts of NPs on the cells of innate and adaptive immunity. The results have shown that the inhalation of CuO NPs significantly alters the composition of cell populations of innate immunity and modulates the proliferation and production of cytokines by cells of the adaptive immune system. However, the immunomodulatory effects of inhaled NPs strongly depend on the time of inhalation.